Pengaruh Price Discount, Bonus Pack, Instore Display, Brand Image Dan Keragaman Produk Batikterhadap Impluse Buying Pada Konsumen Batik UD. Al-Barokah Sumenep - Alqindi, Achmad Hanif; Kurriwati, Nirma (Management Department of Economics and Business Of Trunojoyo Madura University, 2023)
UD. AL- Barokah Sumenep. As shopping center of batik at regency Sumenep that straightforward show batik product result it to consumer. Shopping cester batiks that standing early year 2015 advance expenditure startup concepts local society consumers, by treats various design and heterogeneous pattern beginning of traditional design (Madura), Msdura’s conjugate and java and modern batik. To the effect research aims 1) to Menganalisis is influence price discount to impluse buying on consumer batiks UD. Al Barokah Sumenep. 2. Menganalisis is influence pack's bonus to impluse buying on consumer batiks UD. Al Barokah Sumenep. 3. Menganalisis is influence instore is display to impluse buying on consumer batiks UD. Al Barokah Sumenep. 4. Menganalisis is influence brand is image to impluse buying on consumer batiks UD. Al Barokah Sumenep. 5 Menganalisis is product diversity influence to impluse buying on consumer batiks UD. Al Barokah Sumenep.Approachings observational method quantitative, with SPSS For’s application purpose windows 25 population and sample as much 60 respondents with tech analisis bifilar linear regression data. Result observationaling to point out that Price discount, pack's bonus, instore is display, brand is image and product diversity have influence that signifikan to impulse buying , on UD. Al Barokah Sumenep has to increase signifikan's influence